High-Sensitivity C-Reactive Protein and Cardiovascular Disease - Mohsin, MK; Ahmed, MU (Cardiovascular Journal, 2011)
DOI: http://dx.doi.org/10.3329/cardio.v3i2.9188 Cardiovasc. J. 2011; 3(2): 178-186